Inflammatory cytokine profile of VEGF and IL-6 from the endometrium of women with and without endometriosis - Ashish, Ashish; Kusum, Kusum; Rai, Sangeeta; Zahra, Kulsoom; Mishra, Surendra Pratap; Rai, Gunjan; Chaube, Radha; Singh, Royana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Endometriosis affects an estimated 176 million women worldwide, which constitutes 10% of the total female population causing debilitating symptoms of pelvic pain and infertility, which limits the quality of reproductive life of affected women. The present study aimed to assess the serum level of VEGF and pro-inflammatory marker IL-6 in cases and normal healthy control groups. Methods: VEGF and IL-6 serum levels were measured by competitive sandwich enzyme-linked immunosorbent assay (ELISA) from 34 subjects with surgically confirmed endometriosis, 16 subjects with adenomyosis and 18 similar age matched healthy controls with no clinical evidence of the disease or detectable endometriotic lesions at the time of surgical examination. Patients were characterized in terms of their socio-demographic and clinically diagnosed characteristics, including the validated infertility and chronic disease registries. Results: The mean serum level of VEGF was significantly (p<0.0001) higher in case of endometriosis (3887 ng/l) followed by adenomyosis (2588 ng/l) group and lower in case of normal healthy control (665 ng/l) group. The mean serum IL-6 was found to be highly significant (p<0.0001) in case of endometriosis (90.49 pg/ml) followed by adenomyosis (70.37 pg/ml) group and lower in case of normal healthy control (22.97 pg/ml) group. Conclusions: VEGF and IL-6 seems to play a crucial role in the implantation and development of endometriotic lesions, and the disease is associated with significant modulations in the serum levels of VEGF. IL-6 can be a reliable non-invasive diagnostic marker for endometriosis.